Adjuvant intensity modulated whole-abdominal radiation therapy for high-risk patients with ovarian cancer FIGO stage III: final results of a prospective phase 2 study - Arians, Nathalie; Kieser, Meinhard; Benner, Laura; Katayama, Sonja; Herfarth, Klaus; Schubert, Kai; Schneeweiss, Andreas; Sohn, Christof; Lindel, Katja; Debus, Jürgen (Radiation oncology, 2019)
Background: To assess late toxicity, quality of life and oncological outcome after consolidative whole abdominal radiotherapy (WART) following cytoreductive surgery and carboplatin/paclitaxel chemotherapy in high risk patients with advanced ovarian cancer FIGO stage III using IMRT (Intensity modulated radiation therapy). Methods: The OVAR-IMRT-02 study is a multi-center single-arm phase-II-trial. Twenty patients with optimally debulked ovarian cancer stage FIGO III with complete remission after chemotherapy were treated with intensity modulated WART. A total dose of 30 Gy in 20 fractions was applied to the entire peritoneal cavity. Primary endpoint was treatment tolerability; secondary objectives were acute and chronic toxicities, quality of life, rates of therapy disruption/abortion, progression-free survival (PFS) and overall survival (OS). Results: All patients completed treatment and 10/20 patients (50%) reached the final study follow-up of 36 months. Late side effects consisted of °1-°2 lower limb edema (44.5%), with one patient (5.6%) showing °3 edema. Three patients (16.7%) showed elevated gamma-Glutamyltransferase. There were no severe late side effects regarding renal or hepatic function or any gastrointestinal toxicity greater than °2. During WART, mean global health status decreased by 18.1 points (95%-CI: 7.1–29.0), but completely normalized after 6 months. The same trend was observed for the function scale scores. Kaplan-Meier-estimated 1-, 2- and 3-year PFS was 74, 51 and 40%, respectively. 1-, 2- and 3-year OS was 89, 83 and 83%, respectively. Conclusions: Intensity modulated WART after aggressive surgery and carboplatin/paclitaxel chemotherapy is associated with an acceptable risk of acute and late toxicity and minor impact on long-term quality of life. Together with the promising results for PFS and OS, intensity modulated WART could offer a new therapeutic option for consolidation treatment of patients with advanced ovarian cancer. Trial registration: The study is registered with ClinicalTrials.gov (NCT01180504). Registered 12 August 2010 – retrospectively registered.